EVALUASI PENGGUNAAN FILLER TEPUNG SEREAL DAN ASAP CAIR TEMPURUNG KELAPA PADA KUALITAS DAN DAYA SIMPAN SOSIS IKAN TENGIRI - Yulistyani, Ratna (REKAPANGAN, 2011)
The aims of this study to determine the type and concentration of filler material of  the  cereal  flour  is best  at  making  tengiri  fish  sausage    terms  of   quality  and  power  consumers have received and to evaluate  the  influence of  the concentration of  liquid  smoke to the coconut shell store and the consumer  preference on the level of sausage  products  tengiri  .    The  results  showed   that  the  best  fillers  in  the  manufacture  of  fish sausage was tengiri  cornmeal (Arjuno varieties) with a concentration of 6%, which has  a value of  88% WHC with the appearance test score 3.5; 5.0 smell test; sense of 5.0;  color resilience  5.0  and 2.8.    Minimum  inhibitory  concentration  of  liquid   smoke  to  the  bacteria coconut shell fish sausage tengiri contaminants on  nutrient broth medium with  initial  population  of  10  5  CFU  /  ml  was   0.25%.    Coconut  shell  liquid  smoke  is  more  effective in inhibiting the  growth of bacteria in sausage products when combined with  cold  storage  /   refrigerator  temperature.    The  use  of  coconut  shell  liquid  smoke  concentration 0.5% for the manufacture of fish sausage tengiri already quite  effective  in  inhibiting  the  growth  of  bacteria  at  refrigerator  temperature   storage  preferably  consumers than any other  treatment.Keywords: Sausage, smoked coconut liquid, filler flour cereals, fish tengiri